Influence of Mezzanine Financing on the Corporate Financial Profile - Kirill Gorodnikov; Mikhail Pavlov; Alexander Sus (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2022)
Due to global changes in the global economy, the importance of financing and building an optimal capital structure is increasing. Rapid changes in the exogenous environment and the investment climate lead companies to revise their financing strategies.Currently, there are many financial instruments that provide cash inflow, but have certain restrictions. The tool that allows to eliminate them is the mezzanine. However, the existing literature on mezzanine financing does not fully cover this financing method. The novelty of this research lies in determining the financial profile of the borrower company that utilizes mezzanine financing, and in studying the impact of the mezzanine on the market value of a company’s equity and its value. Econometric analysis confirms that mezzanine financing is more often chosen by companies with a less attractive financial profile, based on ROA, EBITDA – CapEx cash flow, and beta. In addition, the interconnection between a company’s life cycle and its desire to attract a mezzanine loan is revealed. Econometric and empirical analysis allow us to conclude that the market situation, managerial methods within the company and the operational strategy increase the chances of the effective use of the mezzanine.